Examining the significance of visual artifacts in Anlo traditional marriage system in the Volta region of Ghana - Gbadagba, Godwin; Acquah, Ebenezer Kwabena; Empeh-Etseh, Henry (Research Journal in Advanced Humanities, 2020)
This study sought to examine the significance of visual artifacts used in Anlo traditional marriage system in the Volta Region of Ghana. Ethnographic research design embedded in the qualitative paradigm was adopted for the study. The purposive technique was used to sample ten (10) respondents; thus, a chief, an elder, and eight (8) married couples in Anyako. A multi-data collection technique comprising semi-structured interviews and non-participant observation was employed for data collection. The results identified various visual artifacts which were, the marriage stool, the marriage cloths (e.g., Achimotta, Haliwoe, Fiawoyome). Also, the study revealed that the wooden stool, “Atizikpui”, is a symbol of the woman's permanency and that she has come to stay forever. The philosophies and concepts behind these visual artifacts become the norms and ethics which bind society. Similarly, the society is taught to make artifacts not just for their aesthetics but also as a way of preserving the culture of the people. The study recommended that traditional leaders must continue to use occasions like durbars, festivals, and other ceremonies to sensitize their subjects on the importance of preserving their culture. This will educate the Anlos about the significance of visual artifacts in their marriage system and also provide good sources of reference materials for the future generation to continue the legacy.